2013
DOI: 10.1016/j.exer.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simulated cataract light scatter on retinal vessel oximetry

Abstract: To assess the impact of light scatter, similar to that introduced by cataract on retinal vessel blood oxygen saturation measurements using poly-bead solutions of varying concentrations.Eight healthy, young, non-smoking individuals were enrolled for this study. All subjects underwent digital blood pressure measurements, assessment of non-contact intraocular pressure, pupil dilation and retinal vessel oximetry using dual wavelength photography (Oxymetry Modul, Imedos Systems, Germany). To simulate light scatter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…Previous reports have shown that the measurement of arterial and venous retinal oxygen saturation tended to be lower in images of poor quality 16,17. To minimize the effects of cataract in this study, we excluded 26 patients, whose “image quality” was <6.0 before surgery.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports have shown that the measurement of arterial and venous retinal oxygen saturation tended to be lower in images of poor quality 16,17. To minimize the effects of cataract in this study, we excluded 26 patients, whose “image quality” was <6.0 before surgery.…”
Section: Discussionmentioning
confidence: 91%
“…In vivo , Patel et al. () introduced an additional plano lens filled with a polybead solution that simulated light scatter to mimic the changes in lens morphology. The light scatter model used in this study incorporated polybead microspheres, mimicking a forward light scatter similar to that produced by the ultra‐structural features of human lens fibre cells (Costello et al.…”
Section: Discussionmentioning
confidence: 99%
“…We previously explored the effects of scatter on dual‐wavelength oximetry (Patel et al. ) and were able to demonstrate that simulated light scatter alters retinal vessel oximetry parameters. One of the limitations of this study was the small numbers of participants, vessels assessed and image size due to the optical set‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Vessel saturation calculations depend on the absorption spectra, which in turn can be affected by light scatter, media opacity and illumination (Heitmar & Cubbidge ; Patel et al. ). We have previously explored the influence of light scatter using a polybead model (Patel et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation